To reform the world : international organizations and the making of modern states - Sinclair, Guy Fiti (History and theory of international law., 2017)
The book explores how international organizations (IOs) have expanded their powers over time without formally amending their founding treaties. IOs intervene in military, financial, economic, political, social, and cultural affairs, and increasingly take on roles not explicitly assigned to them by law. The proposed book will contend that this 'mission creep' has allowed IOs to intervene internationally, most often in the Global South, in a way that has allowed them to recast institutions within and interactions among states, societies, and peoples on a broadly Western, liberal model. Adopting a historical and interdisciplinary, socio-legal approach, it supports this claim through detailed investigations of historical episodes involving three very different organizations: the International Labour Organization in the interwar period; the United Nations in the two decades following the Second World War; and the World Bank from the 1950s through to the 1990s. The book draws on a wide range of original institutional and archival materials, bringing to light little-known aspects of each organization's activities, identifying continuities in the ideas and practices of international governance across the twentieth century, and speaking to a range of pressing theoretical questions in present-day international law and international relations --Front flap of the book.